Dimensional accuracy of acrylonitrile butadiene styrene and polylactic acid samples printed in vacuum-assisted material extrusion system - Maidin, Shajahan; Shahrum, Mohd Afiq; Rajendran, Thavinesh Kumar; Azri, Mohd Asyraf; Ismail, Shafinaz; Kamarulnizam, Mohd (IOP Publishing Ltd, 2024)
This paper discusses the impact of integrating a vacuum system into a material extrusion 3D printing process for acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) materials. The study aimed to investigate the effect of a vacuum system on the dimensional accuracy of the printed samples. Upon completion of the printing process, the samples’ dimensions were carefully assessed using a Coordinate Measuring Machine (CMM). The geometrical dimensions measured are the diameter, corner radius, fillet, thickness, width, length and angle. Based on the result obtained, the material has yet to reach 100% of the desired geometry, which was identified due to the shrinkage of the material after the printing process. The results show that the vacuum system improved material flow and reduced dimensional deviations by reducing air molecules and minimizing convection. The results indicated a significant enhancement in dimensional accuracy for both ABS and PLA samples when using the vacuum system. ABS samples showed a 4% increase in accuracy, while PLA samples exhibited a 2% improvement compared to samples printed without vacuum assistance. These improvements were achieved by optimizing process parameters such as layer height(0.15 mm), infill percentage (10%), printing speed (45 mm s−1), and bed temperature (60 °C). These parameters were selected to ensure finer details, improved precision, structural support, stability, better adhesion, and reduced warping.